A Comparative Study among Stakeholders Regarding Negative Impact of Municipal Solid Waste Management in Kerala: Assessing the Stakeholders' Perspective on the Negative Impact of Municipal Solid Waste Management in Kerala (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Kerala is known for its high social and human development indices world over. Its high literacy rate, low death and birth rate are setting models for other states of India and are at par with advanced countries. The resident’s household sanitation level is very high but the state’s low environmental sanitation level poses a serious question on the level of social commitment the people possess. The high population density of urban areas make humans and animals highly risk prone for diseases due to the high scale of uncollected and unprocessed waste. Past studies show that almost 80 of the municipal solid waste is neither collected nor processed or disposed. It shows the inefficiency of the solid waste management system of the State. The present study classifies the waste generators into four key groups namely Households, Shop Owners, HotelsRestaurants and Institutions. The negative impact of improper municipal solid waste management is the subject matter of the present study. The major issues are categorized into four types namely Environmental Impact, Air Pollution, Water Pollution and Noise Pollution. It is found that in Environmental Impact HotelsRestaurants are most affected group, while in Air Pollution, Institutions and in Water Pollution and Noise Pollution, Households are the most affected.